Predicting Stock Market by Sentiment Analysis and Deep Learning - Süreyya, Özögür Akyüz; Pınar, Karadayı Ataş; Aymane Benkhaldoun (Operations Research and Decisions)
The stock market may be unpredictable; understanding when to purchase and sell can greatly assist businesses and individuals in maximizing profits and minimizing losses. Many companies have previously modified time-series analysis, a data mining technique, to forecast stock price movement. The idea of textual data mining has recently come up in debates about stock market forecasts. In this study, five of the largest firms' historical stock prices were used to train two deep learning models-long short-term memory (LSTM) and one-dimensional convolutional neural network (1D CNN), then the results of all the models were compared. To connect price value fluctuations with the general public, sentiment scores were offered in addition to stock price values by employing natural language processing techniques (TextBlob) to tweets. (original abstract)